Green roof and photovoltaic panel integration: Effects on plant and arthropod diversity and electricity production. (1st November 2018) - Schindler, Bracha Y.; Blaustein, Leon; Lotan, Ran; Shalom, Hadar; Kadas, Gyongyver J.; Seifan, Merav
Abstract: The combination of green roofs with photovoltaic (PV) panels has been proposed to provide synergistic benefits as the panel is cooled by the presence of the vegetation, and thus produces more electricity, while the solar panel enhances growing conditions for vegetation, and increases abiotic heterogeneity, resulting in higher plant diversity. We tested these hypotheses in a non-irrigated green roof in a Mediterranean climate with replicated plots including green roofs only, green roofs with a PV panel, and a conventional roof surface with a PV panel. We found that presence of a panel resulted in higher heterogeneity in substrate moisture, but there was no effect on plant diversity. Plant species showed enhanced growth in plots with PV, including greater growth of Sedum sediforme and longer flowering time of annual species. On the other hand, arthropod diversity was lower during part of the year, and abundance of some arthropod taxa was lower in green roof plots with PV. The presence of the green roof also did not improve electricity production by the panels. We conclude that in a Mediterranean climate, it would be appropriate to examine the use of irrigation in green roofs with PV panels, including effects on the plant community and on electricity production. Highlights: Presence of a panel resulted in higher heterogeneity in substrate moisture. There was no effect of photovoltaic panel presence on plant diversity. Flowering time of annuals and growth of sedum were enhanced in plots with a panel. Abundance of some arthropod taxa was lower in plots with a photovoltaic panel. The presence of the green roof did not improve electricity production by the panels.